Dried blood spots (DBS): a valuable tool for HIV surveillance in developing/tropical countries. (1st January 2002) - Solomon, Sunil S; Solomon, Suniti; Rodriguez, Irma I; McGarvey, Stephen T; Ganesh, A K; Thyagarajan, S P; Mahajan, Anish P; Mayer, Kenneth H
Dried blood spots (DBS) on filter paper have been used as a practical method of sample collection in sero-surveillance studies of numerous diseases. DBS may be particularly useful for HIV screening in remote areas, in which unrefrigerated transfer time to a laboratory may take a number of days. In this study, we evaluate the ability to detect human immunodeficiency virus (HIV) type-1 antibodies from DBS that have been subjected to a tropical climate in southern India for 6 days. DBS were prepared from blood samples of 59 known HIV-positive individuals and 30 known HIV-negative individuals. ELISA and Western blot results from DBS that were subjected to a mean temperature of 35.8°C and humidity of 73% for 6 days had a sensitivity of 100% and 92%, respectively, and a specificity of 100% and 100%, respectively. Based on these findings, we conclude that DBS sampling could serve as a cost-effective and convenient tool for widespread HIV sero-surveillance in remote areas within tropical countries.